Afro-American Literature: The Analysis of Gorilla, My Love by Toni Cade Bambara - Kustinah Kustinah; Sri Haryanti; Suhud Eko Yuwono; Umi Sholihah (NOTION: Journal of Linguistics, Literature, and Culture, 2021)
It is said that Afro-American literature is the body of literature produced in the United states by writers of African descent. Today, Afro-American literature has become accepted as an integral part of American literature. In broad terms, Afro-American literature can be defined as writings by people of African descent living in the United States. This qualitative study analyzes a short story entitled Gorilla, My Love written by a female Afro-American writer, Toni Cade Bambara. The analysis of the study aims at answering the three problem formulation: (1) states the literariness of the text (2) explains how the literariness of the text play as a means to symbolize a “broader” text (the universe) and (3) writes the proof of mental evidences taken from the text. In analyzing the short story, this study uses Sociology of Literature and Psychology of Literature. The two theories help readers understanding the theme of the short story by reading the explanation about how the narrator of the story set the plot. This study uses narrative as its approach since this is a literary study where a short story is analyzed through its narrative structure. The conclusion of the study provides the proof of its research benefits: giving information to readers about the following: (1) all about Afro-American literature plus its life-experience, family-values, etc. (2) how a literary work can connect its readers to their life and (3) an understanding that a reading-act strengthens the definition that a literary work is as a portrait of human experience.